Trends in global virtual land trade in relation to agricultural products. (March 2020) - Qiang, Wenli; Niu, Shuwen; Liu, Aimin; Kastner, Thomas; Bie, Qiang; Wang, Xiang; Cheng, Shengkui
Highlights: We quantify the arable cropland trade embodied in the global trade of agricultural products. We determine the changing characteristics of the VLT in relation to different product categories and countries. We illustrate the global VLT network's structure and temporal evolution; and provide relative suggestions and implications. Abstract: Trade volume of agricultural products can be used to quantify the virtual land transfers between countries. This study assessed the virtual land trade (VLT) associated with the global trade of agricultural products using specific crop yield of exporting countries and gave insights in characteristics of different products and different countries. In addition, the features of trade connections were also displayed by network analysis. The results showed that the total virtual land within global agricultural trade increased from 128 million hectare (ha) in 1986 to 350 million ha in 2016, the average annual growth rate was 5.73 %. Increases in trade of oil crops contributed the largest share to this. The proportion of exported land area in total harvested land area increased for almost all categories of agricultural products. Countries engaged in global agricultural trade could be divided into three groups, net exporters, net importers and countries with balanced VLT. The net importers could be further divided into the countries with absolutely scarce land resources and the countries with relative scarce resources. All net virtual land exporters are the countries with more land resources per capita, such as the United States, Brazil and Argentina. Income growth and changes in diet structure are main factors driving increases in VLT. The VLT network became more complex over the study period, with the number of import and export nodes increasing continuously, and the cumulative distributions of export and import node strength following power law distributions. The major links and players within national, geographic, and economic groups also changed significantly over the study period. VLT has a deep impact on society, economy and environment, appropriate policies should be taken to make these interlinkages more sustainable for both importers and exporters.